Populism and trade. Issue 4 (4th July 2022) - Churche, Milton; Findlay, Christopher
ABSTRACT: The paper examines the concept of populism and how it is grounded in both democracy and nationalism, with a focus on the implications of its rise for the international trading system. The drivers of the demand for populist politics (economic, cultural, and political) are discussed. The factors facilitating the supply of populist politics are also reviewed. A synthesis is developed, with an interest in identifying common elements across different national experiences. The point is then made that populists are often opposed to 'globalism' but not necessarily to an active participation in trade. The conclusion considers the options for a response to populism, and the challenges populism poses for Australia.